Twenty-five years since the identification of the first SCA gene: history, clinical features and perspectives for SCA1 - Martins, Carlos Roberto, Junior; Borba, Fabrício Castro de; Martinez, Alberto Rolim Muro; Rezende, Thiago Junqueira Ribeiro de; Cendes, Iscia Lopes; Pedroso, José Luiz; Barsottini, Orlando Graziani Povoas; França, Marcondes Cavalcante, Júnior (Arquivos de Neuro-Psiquiatria, 2018)
Spinocerebellar ataxias (SCA) are a clinically and genetically heterogeneous group of monogenic diseases that share ataxia and autosomal dominant inheritance as the core features. An important proportion of SCAs are caused by CAG trinucleotide repeat expansions in the coding region of different genes. In addition to genetic heterogeneity, clinical features transcend motor symptoms, including cognitive, electrophysiological and imaging aspects. Despite all the progress in the past 25 years, the mechanisms that determine how neuronal death is mediated by these unstable expansions are still unclear. The aim of this article is to review, from an historical point of view, the first CAG-related ataxia to be genetically described: SCA 1.
Keywords: Spinocerebellar ataxias; ataxin 1; spinocerebellar degenerations